Pemetaan Lanskap Ilmiah Penelitian Obat Herbal Indonesia (1983–2026): Analisis Bibliometrik: Mapping the Scientific Landscape of Indonesian Herbal Medicines Research (1983–2026): A Bibliometric Analysis - Danang Prasetyaning Amukti; Ria Indah Pratami (Universitas Gunadarma, 2026)
Herbal medicine research in Indonesia has experienced rapid development along with the increasing interest in natural-based treatments and the utilization of biodiversity. This study aims to map the scientific landscape of herbal medicine research in Indonesia during the period 1983–2026 using a bibliometric approach. Data were obtained from the Scopus database with keywords related to herbal medicine, traditional medicine, phytotherapy, and ethnopharmacology combined with the Indonesian context. Analysis was conducted using VOSviewer and Biblioshiny software to evaluate publication trends, journal sources, author productivity, institutional affiliations, citations, and keyword mapping. The results show 659 publications from 333 sources, with an annual growth rate of 6.5%. The publication trend has increased significantly since 2016 and peaked in 2025 with 92 articles. Keyword analysis shows the dominance of topics such as herbal medicine, plant extract, phytochemistry, and antioxidant activity, indicating that the research focus is still at the pre-clinical stage. Publication sources are dominated by proceedings such as the IOP Conference Series (35 articles) and journals such as Biodiversitas (32 articles). The most productive institutions were Airlangga University (95 publications) and Gadjah Mada University (82 publications), with an average of 4.9 authors per article and 17.91% international collaboration. The highest-impact articles received 313 citations, demonstrating the importance of publication in reputable journals. In conclusion, herbal medicine research in Indonesia has shown significant growth but is still dominated by exploratory research. Improvements in publication quality, international collaboration, and strengthening translational research are needed to support the development of evidence-based herbal medicines and enhance Indonesia's contribution globally.